Role of Ayurveda Treatment of Type 2 Diabetes Mellitus: A Case Report - Sharma, Neetu; ram, Sukha (International Research Journal of Ayurveda & Yoga, 2021)
Background: A 49-year-old woman having earlier history of type 2 diabetes with a random sugar level of 323 mg dLG1. Methodology: On the basis of pathology reports, The doctor prescribed metformin HCl (1000 mg) with glimepiride 2mg BD and tenegliptin (20 mg) once a day to patient, even after 7 years, patient complaining to blood sugar raised and doctor advised her for insulin injections. Results: The above treatment was not found satisfactory for the patient, as there was problem in maintaining the sugar level. However, after starting Ayurveda treatment with Chandraprabha Vati, Aamalaki Rasayana, Madhumehari Churna and Pathya Ahara - Vihara followed by yoga practice and morning walk, the patient started to recover very fast and within one month, she achieved better results in blood sugar level. Conclusion: The Ayurveda treatment can be considered as most effective because of its ability to control blood sugar level and also having fewer side effects as compared to that of allopathic medicines